Comprehensive virtual orthognathic planning concept in surgery-first patients. Issue 8 (October 2022) - Ebker, Tobias; Korn, Paula; Heiland, Max; Bumann, Axel
Abstract: The surgery-first concept is becoming increasingly popular in orthognathic surgery since it offers major advantages such as a reduction of treatment duration and an increase in patient satisfaction by eliminating phases of presurgical orthodontic decompensation. Here, we present a novel interdisciplinary pathway of a fully virtual orthodontic-surgical planning concept in a surgery-first setting using a 3D-printed cutting guide and a customised maxillary implant for the Le Fort I osteotomy as well as a CAD/CAM-based stereolithographic final splint. Patient data from cone-beam computed tomography of the skull and a full arch dental scan were processed using the OnyxCeph 3TM software (Image Instruments). A mutual computer-aided surgical simulation was conducted by the orthodontist and the oral and maxillofacial surgeon to determine the three-dimensional maxillary and mandibular movements. In a separate virtual planning session, the surgeon designed a customised maxillary guide and implant for precise intraoperative transfer (Geomagic Freeform Plus software, 3DSystems). A 3D-printed CAD/CAM-based final splint was fabricated by the orthodontist and used for accurate mandibular repositioning. We established a comprehensive virtual interdisciplinary orthognathic workflow and successfully applied this concept with a high level of accuracy in a series of surgery-first patients with different types of dentofacial anomalies. This novel fully computer-based pathway offers a high potential to improve the outcomes of orthognathic surgery and reduce total treatment time in the management of the orthognathic patient.